Integrating hydro-geomorphological adjustments into flood mapping for enhanced risk assessment - Tuhin Mukherjee; N. K. Goel; D. S. Arya; Manohar Arora (Geoenvironmental Disasters)
Abstract Accurate flood risk assessment is essential for effective risk management, especially as extreme rainfall trends have increased flood frequency and inundation globally. However, rainfall data alone often becomes insufficient in dynamic floodplains, where geomorphological changes are critical. The Shilabati River basin in West Bengal, India, illustrates such a landscape, having experienced severe floods in 1959, 1967, 1968, 1973, 1978, 1999, 2000, 2007, 2013, and 2021. For this basin, mapping landform variability is key to understanding erosion and landscape denudation processes. The Digital Elevation Model (DEM)-based technique known as DEM of Difference (DoD) enables the detection of terrain changes over time by comparing DEMs from distinct periods, offering insight into floodplain erosion. However, DEM-based analysis is prone to spatially correlated errors, which can propagate false topographic features, hindering accurate flood mapping. Our study employs the Elevation Deviation Index (EDI), a DEM comparison method that normalizes and mitigates spatially correlated errors across terrain. Using EDI, we mapped geomorphological changes in the Shilabati floodplain, revealing substantial erosion and elevation loss. Our findings demonstrate a strong positive correlation between EDI values and increased flood extent. These results underscore the importance of incorporating geomorphological analysis in flood risk assessment, as hydrological data alone may overlook critical terrain changes. We recommend a Preliminary Flood Risk Assessment (PFRA) to strengthen flood resilience in the region, targeting vulnerable zones for enhanced, adaptive flood mitigation strategies.